Determinants And Consequences of Land Sales Market Participation : Panel Evidence From India - Deininger, Klaus W., 1962- 1962- (The World Bank, 2007)
Although opinions on impacts of land market transfers are sharply divided, few studies explore the welfare and productivity effects of land markets on a larger scale. This paper uses a large Indian panel spanning almost 20 years, together with a climatic shock (rainfall) indicator, to assess the productivity and equity effects of market-mediated land transfers (sale and purchase) compared with non-market ones (inheritance). The analysis shows that frequent shocks increase land market activity, an effect that is mitigated by the presence of safety nets and banks. Land sales markets improved productivity and helped purchasers, many of whom were formerly landless, to accumulate non-land assets and significantly enhance their welfare